METHODOLOGY FOR DETERMINING VEHICLE BRAKING IN TRAFFIC - Khaydarali Fayzullaev (Web of Journals Publishing, 2024)
In this article, based on the theoretical approach developed in the study of the car braking process, it is to increase the performance of the results of the examination of the car transport.
Keywords: Transport, brake, car, truck, result, expertise